An improved UWB Patch Antenna Design using Multiple Notches and Finite Ground Plane - Padmavathy,A.P (2015)
AbstractAn UWB antenna design with finite ground plane approach and multiple notches is reported. The antenna design provided a 10 dB bandwidth in excess of 8 GHz with better return loss characteristics. The antenna implemented in FR4 substrate, is compact and cost effective. The measured antenna parameters are in agreement with simulation.